"Resistance of Single Ag Nanowire Junctions and Their Role in the Conductivity of Nanowire Networks" - BOLAND, JOHN; FERREIRA, MAURO; BELLEW, ALLEN; GOMES DA ROCHA, CLAUDIA (My University, 2015)
Networks of silver nanowires appear set to replace expensive indium tin oxide as the transparent conducting electrode material in next generation devices. The success of this approach depends on optimising the material conductivity, which up to now has largely focused on minimising the junction resistance between wires. However, there have been no detailed reports on what the junction resistance is, nor is there a known benchmark for the minimum attainable sheet resistance of an optimised network. In this paper we present junction resistance measurements of individual silver nanowire junctions, producing for the first time a distribution of junction resistance values, and conclusively demonstrating that the junction contribution to the overall resistance can be reduced beyond that of the wires themselves through standard processing techniques. We find that this distribution shows the presence of a small percentage (6%) of high-resistance junctions, and we show how these may impact the performance of network-based materials. Finally, through combining experiment with a rigorous model, we demonstrate the important role played by the network skeleton and the specific connectivity of the network in determining network performance.
PUBLISHED
Keywords: Silver; Nanowire; Junction; Network; Resistance; Transparent; Conductor; Nanoscience & Materials